An empirical risk and performance analysis of risk parity - Trucksaess, Constantin Leopold Franz Theodor (2022)
This research is conceptualized to provide a comprehensive understanding of the weight allocation mechanism of risk parity. The reader clearly understands why under the equal risk contribution constraint: 1) the asset allocation varies over time, 2) certain assets are penalized, and 3) a risk protection shield is provided. Risk parity is then compared to other robust portfolio strategies based on numerous risk and performance metrics. These back tests cover two sample periods in which risk parity over performs and underperforms. The critical findings are incorporated in a portfolio optimization using a regime-switching signal and trend-following, resulting in superior results in both periods.